Pengaruh Penerapan Standar Akuntansi UMKM Terhadap Kualitas Laporan Keuangan UMKM Pada UMKM Tercatat di Kecamatan Lakarsantri - Marchelo Boas Permata; Wahyu Helmy Dimayanti Sukiswo (Jurnal Ekonomi Manajemen Akuntansi, 2025)
The purpose of this study is to assess how the Financial Accounting Standard for Micro, Small, and Medium Entities (SAK EMKM) has improved the quality of financial statements of businesses in Lakarsantri Sub-district. Using a survey-based quantitative research methodology, information was collected from 40 MSME respondents through questionnaires. Partial Least Square (PLS) analysis was conducted on the data using WarpPLS software version 8.0. The results show that the implementation of SAK EMKM significantly improves the readability, consistency, accuracy, and conformity with accounting standards of MSME financial statements. The results suggest that the application of correct accounting principles can improve the financial transparency and accountability of MSMEs by having a favorable impact on the quality of their financial statements. This study also shows that to support MSMEs' access to financial resources and foster sustainable local economic growth, it is necessary to continue promoting the understanding and application of SAK EMKM. This study also provides strong empirical support for the importance of applying sound accounting principles to produce reliable and quality financial statements.